TOO MANY COOKS: TRUSTING NEW VOICES IN ONLINE CULINARY ADVICE - Kirkwood, Katherine (AoIR Selected Papers of Internet Research, 2019)
Digital technology is becoming increasingly enmeshed in the everyday practices of cooking and eating (see Lewis 2018; Kirkwood 2018). In negotiating the increasingly complex web of culinary information online users need to remain vigilant about the voices and perspectives they turn to for food and nutrition advice. In examining which online sources are trustworthy, this paper adds to the scholarship that highlights how the growing industrialisation of food negatively impacted food literacy (Pollan 2006; Vileisis 2008). In relation to digital food media, Lewis (2018, 214) argues that “food citizens increasingly require a critical media literacy…”. This is important considering that consumers are more likely to turn to the media than nutrition professionals for advice (Contois and Day 2018, 16). This paper builds on Lewis’ (2018) calls for greater critical media literacy Through textual analysis of online news and popular commentary, this paper examines the two Australian case studies of Australian celebrity chef Pete Evans and fraudulent wellness advocate Belle Gibson. These examples highlight risks associated with online culinary information and provide contrasting perspectives on credibility and trustworthiness. Evans leverages mainstream media exposure and experience as a chef to establish credibility for his online channels where he explores his alternative culinary views more extensively. Gibson’s reputation meanwhile was established through achieving grassroots fame online for supposedly beating cancer through shunning conventional treatments. Understanding how trustworthiness or authority is established and negotiated, and particularly how these characteristics work between legacy and online media are important in developing critical media literacy around food.